2018
DOI: 10.1002/pc.24981
|View full text |Cite
|
Sign up to set email alerts
|

Sound absorption properties of nonwoven fabric based multi‐layer composites

Abstract: In this article, the sound absorption properties of multi‐layer fibrous composites consist of nonwoven fabric, woven fabric and polyethylene (PE) membrane was investigated. Six types of different constructions including both bi‐layer and three‐layer structures were tested by impedance tube ranged from 100 to 6,300 Hz. To improve the sound absorption of multi‐layer composites, the effects of layering sequence, woven fabric and PE membrane were studied. It has been found that layering sequence is important for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Furthermore, SPCs can be completely melted and when it comes to recycling, this property is a great advantage compared to, for example, carbon or glass fibre reinforced composites, whose mechanical and thermal recycling still causes environmental problems [8]. In the near future, these SPCs and melt-blown fibre mats can significantly contribute to a wide range of applications, for example tissue scaffolds [9], filtering applications [10], superhydrophilic membranes [11,12], sound absorption [13] and ductile & impact-resistant components [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SPCs can be completely melted and when it comes to recycling, this property is a great advantage compared to, for example, carbon or glass fibre reinforced composites, whose mechanical and thermal recycling still causes environmental problems [8]. In the near future, these SPCs and melt-blown fibre mats can significantly contribute to a wide range of applications, for example tissue scaffolds [9], filtering applications [10], superhydrophilic membranes [11,12], sound absorption [13] and ductile & impact-resistant components [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…[ 107,109 ] Changes in the reinforcing architecture of the fibers lead to changes in their acoustic properties. [ 14,17,104,105 ] The coir fiber had a good sound absorption coefficient and transmission loss index value, according to the acoustic property results. The coir fiber's arrangement can be changed to modify the sound absorption capabilities.…”
Section: Effect Of Reinforcement Architecture On the Acoustic Behaviormentioning
confidence: 99%
“…The study had shown that closedcell polyurethane foams with membranes had better acoustic properties than the open-cell ones with similar parameters in the 500-6000 Hz frequency range. In addition, Tang et al [20] improved sound absorption of layered materials composed of nonwoven fabrics and polymeric membrane by adjusting the layering sequence. A research found that the characteristic absorption peaks shifted to the lower frequency by tuning the layer thickness and thickness ratio of the microlayer foam/film sheet materials [21].…”
Section: Introductionmentioning
confidence: 99%